'A most venerable ruin': word, image and ideology in Guest's Geraint the son of Erbin. (1st December 2019) - Davies, Sioned
Lady Charlotte Guest's translation of Geraint the son of Erbin, published as part of a threevolume edition in 1849, was illustrated by the wood-engraver Samuel Williams. Drawing on theoretical paradigms from illustration studies, the relationship between word and image is explored, highlighting how illustrations create a complex dialogic relation between image and text. Questions are then raised as to why, in Guest's second edition of the tale, in 1877, changes and adjustments were made, specifically to those elements related to the ruins of Cardiff Castle. The wider implications of choices relating to the placement of images and the producing of captions, existing as they do in a liminal zone, located between the image and the text, are demonstrated.